Blood Cytomorphometry and Cytomorphology Red-tailed Green Viper (Trimeresurus insularis) On the Bali Island - Limanto, Alvin; Suartini, I Gusti Ayu Agung; Sari, Tri Komala (Jurnal Veteriner; Vol 25 No 4 (2024)DO - 10.19087/jveteriner.2024.25.4.541, 2025)
Snakes  are  becoming  increasingly  popular  among  reptile  enthusiasts  due to  their uniqueness  and  exoticism.  Snakes  can  be  classified  into  venomous and  non-venomous. Venomous  snakes  exhibit  unique  colors,  body  shapes, and  behavior.  Snake  bites  are common  in  Indonesia,  and  many  cases  go unreported.  The  red-tailed  green  viper ( Trimeresurus insularis/T. insularis ), a venomous snake, is frequently found on the island of Bali.  However,  research  on  this  snake  is  limited.  Blood  morphology  is  an  indicator  of  an animal's health  status  and  can  provide  comprehensive  information  about  the  animal.  The study  was  aimed  to  know  the  cytomorphology  and cytomorphometry  of  Red-tailed  Green Viper ( Trimeresurus insularis ) on the Bali Island.  Knowing the health status of T. insularis through the morphology of its blood cells can assist veterinarians in diagnosing and treating sick  animals.  This study  used  nine  healthy  T.  insularis  snakes,  comprising  five  males  and four females  from  Bali.  Blood  was  collected  from  the  coccygeal  vein  smeared on  a  glass slide,  fixed  with  90%  ethanol,  and  stained  with  10%  Giemsa.  The blood  smear  was  then observed  under  a  microscope  to  measure cytomorphometry.  The  Veterinary  Immunology Laboratory  at  Udayana University  and  the  Malang  Healthy  Animal  Clinic  conducted  cell measurements  using  an  Olympus  CX33  microscope,  analyzing  data  with SPSS  via  the Analysis  of  variance  test.  The  study  found  significant differences  in  erythrocyte  nucleus width  between  male  (25.92  µm)  and female  (30.44  µm)  T.  insularis  snakes,  as  well  as  in basophil cytoplasm length (males: 6 µm, females: 5.37 µm). No differences were observed in  heterophils, lymphocytes,  or  azurophils,  and  eosinophils  were  absent  in  these  snakes  on Bali.